The Effects of SLS on Structural and Complex Permittivity of SLS-HDPE Composites - Abubakar Dantani Meli; Zulkifly Abbas; Mohd Hafiz Mohd Zaid; Nor Azowa Ibrahim (Advances in Polymer Technology)
RS-4050 is a rigid epoxy based magnetic castable microwave absorbing material; it has been used in many areas of waveguide application as a microwave waveguide terminations and dummy loads. In recent years, there is a demand for composites material with lower dielectric constant higher loss factor for microwave application. This research, the effect of soda lime silica (SLS) on structural and complex permittivity of soda lime silica-high density polyethylene (SLS-HDPE) composites was conducted in order to explore the possibility of substituting RS-4050 with SLS-HDPE composites as a microwave waveguide terminations and dummy loads. Elemental weight composition of the SLS glass powder and HDPE was identified through scaling of different percentage of SLS and HDPE. X-ray diffraction (XRD) was used to investigate the crystallinity behavior of SLS-HDPE composites. The proposed SLS-HDPE composites material was studied at frequencies 8 to 12 GHz. The study was conducted using waveguide Agilent N5230A PNA technique. The effect of microwave frequency on complex permittivity properties for SLS-HDPE composites of different percentages of SLS and HDPE (10% SLS-90% HDPE, 20% SLS-80% HDPE, 30% SLS-70% HDPE, 40% SLS-60% HDPE, and 50% SLS-50% HDPE) were investigated. Results showed the diffraction patterns reveal good amorphous quality with a genuinely properties structure. The microwave frequency and composites percentages significantly influenced the complex permittivity (real and imaginary) properties of the composites. Moreover, the complex permittivity increased as the percentage of SLS filler increased in the host matrix HDPE as a result of increased in composite density due to less volume being occupied by the filler as the percentage increased. The complex permittivity of the smallest and largest percentages of SLS (10% and 50%) was (2.67-j0.05) and (3.45-j0.35), respectively. The study revealed that the best sample for waveguide application as microwave terminator is 50% SLS as it has the highest dielectric constant, highest loss factor, and highest loss tangent as compared to 10% SLS to 40% SLS. Also 50% SLS has the highest absorption properties as compare to 10% SLS, 20% SLS, 30% SLS, or 40% SLS. The XRD physical structure of the SLS-HDPE composites revealed the absorption characteristics of different percentages of the materials. The SLS-HDPE composites can be applied in the area of waveguide as a microwave waveguide terminations and dummy loads.